GE_GERICHTE P/5484/2012 vom 29. November 2013 - GE Cour de justice (2013)
ADMINISTRATION DES PREUVES; APPEL(CPP); ACTE D'ACCUSATION; DISPOSITIONS PÉNALES DE LA LSTUP | LStup.19; CPP.389; CPP.9.1; CPP.325